New Developments in the Management of Cutaneous Squamous Cell Carcinoma. Issue 3 (23rd February 2021) - Knackstedt, Thomas J.; Knackstedt, Rebecca W.; Djohan, Michelle; Djohan, Raisal; Gastman, Brian R.; Crowe, David R.
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. List important prognostic features that affect cutaneous squamous cell carcinoma risk. 2. Summarize the changes to the AJCC Cancer Staging Manual, Eighth Edition, staging system for cutaneous squamous cell carcinoma. 3. Evaluate the draining nodal basin with appropriate imaging modalities. 4. Recommend adjuvant radiation therapy in the correct clinical setting for high-risk tumors. 5. Recognize the currently available treatments for advanced cutaneous squamous cell carcinoma. Summary: This continuing medical education article reviews the features, management, and prognosis of cutaneous squamous cell carcinoma with an emphasis on high-risk squamous cell carcinoma and data from the past 3 years. This review will discuss the primary tumor management, high-risk features of a squamous cell carcinoma, changes to the American Joint Committee on Cancer staging system, and the utility of sentinel lymph node biopsy, and critically review the evidence regarding adjuvant therapy.